2012
DOI: 10.3389/fneur.2012.00051
|View full text |Cite
|
Sign up to set email alerts
|

Glucoregulatory Consequences and Cardiorespiratory Parameters in Rats Exposed to Chronic–Intermittent Hypoxia: Effects of the Duration of Exposure and Losartan

Abstract: Background: Obstructive sleep apnea (OSA) is associated with glucose intolerance. Both chronic sleep disruption and recurrent blood oxygen desaturations (chronic–intermittent hypoxia, CIH) may cause, or exacerbate, metabolic derangements. Methods: To assess the impact of CIH alone, without accompanying upper airway obstructions, on the counter-regulatory response to glucose load and cardiorespiratory parameters, we exposed adult male Sprague-Dawley rats to CIH or sham room air exchanges for 10 h/day for 7, 21,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…The pathogenesis of β cell dysfunction during IH has been attributed to oxidative stress, apoptosis of β cells and up-regulation of the renin-angiotensin system (Wang et al , 2013;Xu et al , 2009;Yokoe et al , 2008;Fenik et al , 2012). Our data suggest that the impairment of insulin secretion in IH is caused by the surge in circulating epinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of β cell dysfunction during IH has been attributed to oxidative stress, apoptosis of β cells and up-regulation of the renin-angiotensin system (Wang et al , 2013;Xu et al , 2009;Yokoe et al , 2008;Fenik et al , 2012). Our data suggest that the impairment of insulin secretion in IH is caused by the surge in circulating epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously developed a mouse model of chronic IH, which mimics the oxyhemoglobin saturation profile in patients with OSA (Jun et al , 2010;Polotsky et al , 2006;Reinke et al , 2011;Tagaito et al , 2001). Acute and chronic IH induces insulin resistance in mice (Polotsky et al , 2003;Iiyori et al , 2007;Drager et al , 2011;Polak et al , 2013;Lee et al , 2013) and impairs glucose stimulated insulin secretion in mice and rats (Polak et al , 2013;Lee et al , 2013;Fenik et al , 2012). Yokoe et al reported that IH induces replication of pancreatic β-cells (Yokoe et al , 2008), whereas Xu et al reported increases both in β-cell apoptosis and proliferation (Xu et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to an increased NE terminal density and increased α 1 -adrenoceptor expression, CIH could also increase the baseline levels of catecholamines in the brain because, in other studies, CIH exposure resulted in increased plasma levels of catecholamines and increased baseline activity of the sympathetic system (72, 148, 149, 151, 495). However, in Wistar-Kyoto rats, only dopamine levels were increased, whereas NE or 5-HT levels were not, following hypocapnic CIH when measured in tissue homogenates collected from different brain regions (303).…”
Section: Neural Control Of the Upper Airway In Sleep-disordered Breatmentioning
confidence: 98%
“…Blood glucose was determined using a glucometer (Accu-Check Aviva; Roche, Indianapolis, IN) at 0, 10, 20, 30, 60, 90, and 120 minutes after intraperitoneal injection of 1 g/kg glucose (n = 10 per group) or at 0, 10,20,30,40,50,60,90, and 120 minutes after intraperitoneal injection of 0.5 IU/kg insulin (ITT; n = 10 per group).…”
Section: Intraperitoneal Glucose and Insulin Tolerance Testsmentioning
confidence: 99%
“…Several animal studies have suggested that exposure to intermittent hypoxia (IH) compromised whole-body glucose homeostasis, reducing insulin sensitivity, glucose tolerance, and muscle glucose uptake; at the same time, it elevated fasting blood glucose, augmenting hepatic glucose release, and impairing secretion from pancreatic b cells (6)(7)(8)(9)(10)(11). Similarly, exposure of healthy human volunteers to IH for 5 hours induced insulin resistance and impaired pancreatic b cell function (12).…”
mentioning
confidence: 99%